Memperkuat Kemampuan Menulis Guru di Era Digital Melalui Pelatihan Kecerdasan Buatan - Suryadi, Agus; Febrianti, Eka Lia; Sikumbang, Alex Sandri (ASOSIASI IDEBAHASA KEPRI, 2024)
In the digital era, effective writing skills are becoming increasingly important for teachers, especially at SMP IT Nurul Muhajirin Batam, to produce quality learning materials, communicate with students and parents, and engage in professional development. This training aims to explore the potential of artificial intelligence (AI) training in strengthening teachers' writing skills in the digital era. This research uses qualitative methods with a case study at SMP IT Nurul Muhajirin Batam. Data was collected through interviews with teachers, classroom observations, and document analysis. Research findings show that AI training can help teachers improve their writing skills in several aspects, such as grammar, sentence structure, and vocabulary use. AI training also helps teachers produce more creative and engaging content for students. AI training is a promising tool for strengthening teachers' writing skills in the digital era. Further research is needed to explore the effectiveness of AI training in different educational contexts.